MANFAAT LATIHAN YOGA BAGI SISWA PARIWISATA (Studi Kasus SMK Bali Dewata) - I Putu Suyasa Ariputra (UHN IGB Sugriwa Denpasar, 2021)
The rapid development of Yoga is currently being looked at by several groups as an alternative in the development of spiritual tourism. Despite the many contradictions against Yoga as spiritual tourism, the purpose of incorporating Yoga teachings into learning in tourism schools is not only to provide tourism workers who have the ability to meet market needs but also to develop students' interests and talents towards Yoga. Starting from the explanation above, the focus of this research is to see the benefits of yoga practice for tourism students at SMK Bali Dewata. The aim is to describe the benefits that tourism students get after participating in Yoga practice. This study was designed using a qualitative approach by displaying the management of the results of observations, interviews, and literature in the form of word descriptions.Yoga practice carried out by tourism students at Bali Dewata Vocational School is broadly divided into three stages, namely: the initial stage where students are invited to pray and are given initial information about Yoga practice, then the core activity is carrying out Yoga exercises, and ends with Sawasana, affirmations , question and answer, and prayer. The tangible benefit is that tourism students have Yoga skills that are useful for themselves and those around them. Tourism practitioners, especially tourism service providers, have a strategic position to develop Yoga opportunities as spiritual tourism. A qualified ability for a provider of tourism students can certainly be an added value when entering the world of work, glancing at the growing popularity of Yoga among tourists. The intangible benefits are physical fitness and maturity of mental attitude in dealing with something. This is useful as students who later become service providers in the field of tourism. Keywords: Benefits, Yoga, Tourism Students